Postoperative Transient Intractable Hyperacusis in Posterior Cingulate Gyrus Lesion Causing Partial Complex Seizure - Chowdhury, Forhad Hossain; Haque, Md Raziul (Journal of Bangladesh College of Physicians and Surgeons, 2017)
A young man of 19 who underwent surgical excision of a small right posterior cingulate gyrus cystic lesion for complex partial seizure. Postoperatively he developed intractable hyperacusis and persisted for several days. Here we report the case of post operative intractable hyperacusis that developed after surgery in posterior cingulate gyrus and in the literature probably this is the first report of hyperacusis related to posterior cingulate gyrus surgery. J Bangladesh Coll Phys Surg 2016; 34(4): 225-227